Urolithiasis in southern Thailand - Tanthanuch, Monthira (Insight Urology, 2005)
Objective: To address the incidence and epidemiology of urolithiasis in southern Thailand. Design: Descriptive study Materials and methods: The incidence of urolithiasis during 1998 - 2002 was analysed from data of the Ministry of Public Health. For epidemiologic study, over one-year period, urolithiasis patients searching for treatment in Songklanagarind Hospital were enrolled, the data of the patients were described. For stone composition study, calculi from operative theater and ESWL Unit (Extracorporeal Shock Wave Lithotripsy) of Songklanagarind Hospital were analysed with infrared spectroscopy Results: The province with highest incidence of urolithiasis in the South is Satoon in 2002. The common age group is 41-60 year-old, ratio of male to female is 1.5 : 1 and farmer is the most common occupation found in urolithiasis patients. 53.7% of the patients has recurrent stone in 2 years and 42.3% has BMI > 25.0. The diagnosis revealed, 57.4% as renal calculi, 39.1% as ureteric calculi and 3.5% as vesical or urethral calculi. Most of the patients were treated by non-invasive and endoscopic surgery. The most common component for pure stone of upper tract calculi is oxalate, whereas lower tract calculi is uric acid. Conclusion: The province needed exploration in urolithiasis is Satoon, because of the highest incidence. Most of common age group of urolithiasis patients in southern Thailand is 41-60 year-old, male to female ratio is 1.5 : 1. The most common component for pure stone of upper tract calculi is oxalate, whereas lower tract calculi is uric acid. Common component for mixed stone of upper tract and lower tract calculi are oxalate and phosphate.